Analisis Pengaruh Profitabilitas, Ukuran Perusahan, dan Struktur Aktiva terhadap Struktur Modal PT HM Sampoerna Tbk tahun 2004-2019 - Fauziah, Sheilla Nurul; Sari, Maya (Ekspektra : Jurnal Bisnis dan Manajemen, 2021)
Capital structure is an important aspect that determines firm value, therefore companies must give the eye on capital structure so that funding activities can be more efficient. This research aims to identify and analyze the description of the development of the capital structure of PT HM Sampoerna Tbk in 2004-2019 and to analyze the effect of profitability, company size and asset structure on capital structure. The method used is a quantitative method with multiple linear regression data analysis techniques. The results showed that profitability and firm size had a negative effect on capital structure, while asset structure had a positive effect. Simultaneously, profitability, firm size, and asset structure have a significant effect on capital structure, however partially the effect of profitability, firm size and asset structure on capital structure is not significant. Based on the result, to create maximum impact on capital structure, profitability, company size, and asset structure must run hand in hand.